Refreshing Nahwu Knowledge: PowerPoint as a Learning Tool for Arabic Education Students with a PMDG Background - Ahmad Gagah Gattuso; Muhammad Syamsul Arifin; Khoirul Fata; Tuğçe Ceylan (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
Many students in the Arabic Language Education Department (ALED) at Unversitas Darussalam Gontor who graduated from Pondok Modern Darussalam Gontor (PMDG) have learned nahwu by using the modern book an-Nahwu al-Wādih. This book was an important part of their grammar studies during their time at the pesantren. However, after moving on to university-level education, many of them seem to forget the rules they once learned, possibly because they no longer study the material in depth or use it regularly. This study looks into how PowerPoint slides, made in a simpler and more visual format, can help these students remember nahwu rules they already learned in the past. The research was carried out with 40 participants obtained through quote sampling, all of whom are current students in the ALED at Universitas Darussalam Gontor and also alumni of PMDG. Each student took a pre-test to see how much they still remembered. Then, they studied a set of PowerPoint slides designed to explain nahwu in a clearer way. After that, they took a post-test. The results showed that most students did better on the post-test than on the pre-test. This means the PowerPoint slides helped them remember the material. Many of them also said that the slides were easier to understand and nicer to look at compared to reading from the book. This shows that using PowerPoint can be a useful way to help students refresh their grammar knowledge, especially if they have already learned it before.